Protein- and Peptide-Based Virus Inactivators: Inactivating Viruses Before Their Entry Into Cells - Su, Xiaojie; Wang, Qian; Wen, Yumei; Jiang, Shibo; Lu, Lu (Frontiers in Microbiology, 2020)
Infectious diseases caused by highly pathogenic enveloped viruses, such as human immunodeficiency virus (HIV), have posed a serious threat to global public health. Most antiviral drugs act as passive defenders to inhibit viral replication inside the cell, while a few of them function as gate keepers to combat viruses outside the cell, including viral fusion inhibitors, such as enfuvirtide, and receptor blockers, e.g., maraviroc, as well as virus inactivators. Different from fusion inhibitors and receptor blockers, virus inactivators are able to actively inactivate cell-free virions in the blood, through interaction with one or more sites in the envelope glycoprotein (Env) on virions. Notably, a number of protein- and peptide-based virus inactivators (PPVIs) under development are expected to have a better utilization rate than the current antiviral drugs, and be safer for in vivo human application than the chemical-based virus inactivators. In this review, we have highlighted recent progress in the development of PPVIs against several important enveloped viruses, including HIV, influenza virus, dengue virus (DENV), Zika virus (ZIKV) and herpes simplex virus (HSV), and the potential use of PPVIs for urgent treatment of infection by newly-emerging or re-emerging viruses.